49 Aberrant Expression of CD5 in the Setting of B-Cell Acute Lymphoblastic Leukemia: A Case Report and Brief Review of the Literature. (11th January 2018) - Staley, Elizabeth; McIntosh, Eleanor; Hill, Benjamin
Abstract: Background: B-cell lymphoblastic leukemia (B-ALL) classically presents as a neoplastic proliferation of lymphoblasts expressing B-lineage markers and involving the bone marrow and peripheral blood. Immunophenotypic aberrancies are not uncommon in B-ALL, and coexpression of myeloid lineage markers is not unusual (86.5% of cases). Expression of T-cell lineage markers is less common (10% of cases), while the expression of the CD5 antigen is exceptionally rare. Patient: A 13-year-old girl presented with leukocytosis, anemia, and thrombocytopenia. Her peripheral blood flow cytometry was significant for 78% blasts. Bone marrow biopsy and cerebrospinal fluid analysis confirmed the diagnosis of CD5+ B-ALL with central nervous system (CNS) involvement, expressing complex cytogenetics. The patient received induction chemotherapy and achieved remission four weeks post-therapy. She relapsed after 13 months (87% blast in the bone marrow, with CNS involvement); neoplastic cells expressed CD45, CD10, CD19, CD5, CD20, CD22, CD34, and nuclear Tdt, with absent expression of cytoplasmic CD3. The patient underwent re-induction therapy, and again achieved remission. However, she relapsed a second time. CAR T-cell therapy was attempted; however, she experienced treatment complications. The patient ultimately succumbed to disseminated infection secondary to her disease 23 months following diagnosis. Results: A total of 16 cases of CD5+ B-ALL have been described in the literature, with detailed reports existing for only six cases. CD5+ B-ALL may occur more frequently in pediatric patients (65% n = 17), and be associated with a poor prognosis (67% n = 12). Cytogenic anomalies were commonly reported (70% n = 13). Conclusions: Although there are limited data available given the rarity ofCD5+ B-ALL, evidence suggests aberrant CD5 expression is a poor prognostic indicator. Additional research is required to determine whether CD 5+ B-ALL represents a uniquely aggressive subcategory of B-ALL. Furthermore, the CD5 antigen represents a potential target for monoclonal antibody therapy.